Subcutaneous mastectomy, indications and technique - Hornblas, Juan J; Trostchansky, José (Cirugía del Uruguay, 1984)
The subcutaneous mastectomy has very precise in• dlcatlons still under study, in what concerns the treat• ment of high risk mastopathia, as well as the treatment of the contralateral mammary gland in cases of mas• tectomy by neoplasm.